In situ diode laser fenestration: An ex‐vivo evaluation of irradiation effects on human aortic tissue. Issue 9 (30th June 2019) - Piazza, Roberta; Micheletti, Filippo; Condino, Sara; Magni, Giada; Berchiolli, Raffaella N.; De Simone, Paolo; Ferrari, Vincenzo; Ferrari, Mauro; Pini, Roberto; Rossi, Francesca
Abstract: The in situ laser fenestration is an interesting option for the endovascular treatment of short‐necked aneurysms with an intraoperative modification of a standard endograft. According to literature evidence, diode laser emitting in the near‐infrared wavelength (810 nm) can be successfully used to fenestrate the endograft fabric. This paper describes a three‐dimensional navigation system for the accurate targeting of the fenestration site, then reports results of an ex vivo study to assess whether the laser operative conditions, which ensure the fabric fenestration, are harmless for the biological tissue surrounding the endoprosthesis. Two hundred twenty‐five samples of human aorta, including healthy specimens and abdominal aortic aneurysm samples, were irradiated ex vivo using a 810 nm diode laser. Energy and pulse duration were varied. Irradiated tissues were fixed in formaldehyde, sectioned and subjected to histological examination. Only 7.5% of the irradiated samples exhibited a thermal damage, which was always confined to the contact point between the laser fiber tip and the aortic wall. These experiments suggest that the diode laser can be safely used for the proposed surgical application. Abstract : The in situ diode laser fenestration of a standard stent graft is an alternative option in order to avoid custom fabrication of endoprosthesis and find a simple, accurate and cost‐effective way to obtain fenestrated stent grafts preserving blood flow to essential visceral arteries. The laser technology provides the surgeon with a selective fenestration tool without damaging the surrounding tissue.